2020
DOI: 10.1371/journal.pgen.1008583
|View full text |Cite
|
Sign up to set email alerts
|

The nanophthalmos protein TMEM98 inhibits MYRF self-cleavage and is required for eye size specification

Abstract: The precise control of eye size is essential for normal vision. TMEM98 is a highly conserved and widely expressed gene which appears to be involved in eye size regulation. Mutations in human TMEM98 are found in patients with nanophthalmos (very small eyes) and variants near the gene are associated in population studies with myopia and increased eye size. As complete loss of function mutations in mouse Tmem98 result in perinatal lethality, we produced mice deficient for Tmem98 in the retinal pigment epithelium … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Interestingly, all three identified missense variants in TMEM98 have involved proline substitution within helix 5 of the protein, which would be expected to alter the folding of this region of the protein. TMEM98 interacts with MYRF (another nanophthalmos gene product) in the retinal pigment epithelium (RPE) and oligodendrocytes in the brain 8 , 14 , 43 , though the interaction domain is dependent on the N-terminus of TMEM98 and not these C-terminal binding regions 44 . However, it is possible that a protein–protein interaction between TMEM98 and another protein leads to eye specific disease.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all three identified missense variants in TMEM98 have involved proline substitution within helix 5 of the protein, which would be expected to alter the folding of this region of the protein. TMEM98 interacts with MYRF (another nanophthalmos gene product) in the retinal pigment epithelium (RPE) and oligodendrocytes in the brain 8 , 14 , 43 , though the interaction domain is dependent on the N-terminus of TMEM98 and not these C-terminal binding regions 44 . However, it is possible that a protein–protein interaction between TMEM98 and another protein leads to eye specific disease.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, RNA-Seq analysis revealed that Prss56 and Adamts19 were the top two differentially expressed genes between Prss56 mutant ( Prss56 -/- ) and control ( Prss56 +/- ) retina. Besides Prss56 , Tmem98 was the only other differentially expressed gene that has previously been implicated in nanophthalmos [ 8 , 25 ] and was found to be significantly downregulated in the retina from Prss56 -/- mice compared to control Prss56 +/- mice ( S1 Table ). Interestingly, TMEM98 , which encodes a single transmembrane protein of unknown function, is also one of the several loci associated with high myopia in genome-wide association study (GWAS) [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, TMEM98 , which encodes a single transmembrane protein of unknown function, is also one of the several loci associated with high myopia in genome-wide association study (GWAS) [ 12 ]. Notably, conditional ablation of Tmem98 from the RPE, leads to significant increase in ocular size and axial length [ 8 ]. Thus, it is possible that the reduced Tmem98 expression detected in Prss56 -/- mice might have resulted from the differential expression in the fraction of RPE attached to the isolated retina for RNA-Seq analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cross and colleagues did just that in a study published in April 2020's issue of PLOS Genetics [15]. The authors provide yet another surprising, but not unexpected finding, that mice lacking Tmem98 have greatly enlarged eyes with long axial length.…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 97%